Working fluid selection and extensive sensitivity analysis for the thermodynamic optimization of a novel trigeneration cycle with two-phase expanders and compressors - Briola, Stefano; Gabbrielli, Roberto; Fino, Andrea; Bischi, Aldo; Di Marco, Paolo (Energy, 2019)
An extensive investigation of a novel thermodynamic trigeneration cycle, operating with two-phase expanders and compressors and single-component wet working fluids, is carried out. Among the available fluids in the commercial software Aspen Plus 9.0® database and commonly used in industrial applications, four chemical species are selected according to several criteria in order to ensure the technical feasibility of the thermodynamic cycle. Using Aspen Plus 9.0®, an extensive sensitivity analysis in steady state conditions considering six process parameters is carried out for each selected working fluid. The combined effects associated to the process parameters on several energy performance indicators are described. To this purpose, the Parallel Coordinate Plots (PCPs) and energy performance maps associated to each indicator are adopted in original way. For each working fluid, each PCP allows the selection of the arrays of the process parameters corresponding to high values of the respective indicator. Each energy performance map allows determining the working fluid associated to the respective maximum indicator in function of the temperatures of the trigenerative end-user and external environment. The proposed method of analysis is a useful and new tool for similar investigation associated to a generic thermodynamic cycle.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Aspen plus; Parallel coordinate plot; Sensitivity analysis; Thermodynamic cycle; Trigeneration; Two-phase fluid